Valve selection in aortic valve endocarditis - Perrotta, Sossio; Zubrytska, Yana (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Aortic prosthetic valve endocarditis (PVE) is a potentially life-threatening disease. Mortality and incidence of infective endocarditis have been reduced in the past 30 years. Medical treatment of aortic PVE may be successful in patients who have a prompt response after antibiotic treatment and who do not have prosthetic dysfunction. In advanced stages, antibiotic therapy alone is insufficient to control the disease, and surgical intervention is necessary. Surgical treatment may be lifesaving, but it is still associated with considerable morbidity and mortality. The aim of surgery is to perform a radical excision of all infected and necrotic tissue, reconstruction of the left ventricle outflow tract, and replacement of the aortic valve. There is no unanimous consensus on which is the optimal prosthesis to implant in this context, and several surgical techniques have been suggested. We aim to analyze the efficacy of the surgical treatment and discuss the issue of valve selection in patients with aortic valve endocarditis.